Provision of Online Public Access Catalogs for Effective Utilization of Library Resources in Three University Libraries in Nigeria. Issue 3 (2nd April 2017) - Mole, Austin-Jude Chikodi; Mesagan, Faith Olanike
ABSTRACT: The study was carried out to assess the provision of online public access catalog for effective use of library resources in three university libraries in Nigeria. The objectives of the study were to find out the online public access catalogs provided; the resources available for effective provision of online public access catalogs; the extent to which the provision of online public access catalogs have contributed to the effective use of library resources; the problems associated with the provision of online public access catalogs; and strategies for improving the provision of online public access catalogs in the libraries. A descriptive survey design was used for the study. Purposive sampling was used to select three federal universities, including University of Lagos, Obafemi Awolowo University, Ife, and the University of Ibadan. A structured questionnaire and observation checklist were developed based on the research questions and used to obtain data for the study. All data collected through the questionnaire were analyzed using simple statistics (mean). The study findings show that federal university libraries under study have online public access catalogs functioning to a great extent and that through direct access to library bibliographic databases, timely access to library materials, and resource sharing, among others, online public access catalogs have greatly contributed to the effective use of the library resources. However, database conversion, unstable power supply, consistent systems breakdown, and inadequate computers, are among the problems associated with provision of online public access catalogs to support the use of library resources in the university libraries. Based on the findings, it was recommended that the libraries should seek funding from external bodies; catalogers should be exposed to skill acquisition platforms to acquire the competencies required for provision of online public access catalogs, and advances in use of the tools for online public access catalogs should be included in the curricula of library schools in Nigeria.